Ethics in governance - India.Second Administrative Reforms Commission (New Delhi, 2007)
This book tends to address such dilemmas, threats and challenges in a rather systematic and elucidate manner. It attempts to construct perspectives that may find practical solutions to governance complexities and moral conflicts. This is a book full of people, many of them who took part in a national seminar on 'Ethical dimensions of governance' organized at India International Centre: executives, politicians, jurists, media people, medical practitioners, academicians, and organizational heads. Those who were philosophically as well as emotionally interested in the inter-faith debate and who believed in creating a synthesis of different belief systems on governance.
Keywords: Ethics-Governance